Ginsenoside Rg1 attenuation of neurogenesis disorder and neuronal apoptosis in the rat hippocampus after spinal cord injury may involve brain-derived neurotrophic factor/extracellular signal-regulated kinase signaling. Issue 5 (22nd March 2023) - Xi, Bin; Fu, Jieping; Wan, Dengfeng; Xie, Zhiping
Abstract : Objective: We previously demonstrated that spinal cord injury (SCI) induced hippocampus injury and depression in rodents. Ginsenoside Rg1 effectively prevents neurodegenerative disorders. Here, we investigated the effects of ginsenoside Rg1 on the hippocampus after SCI. Methods: We used a rat compression SCI model. Western blotting and morphologic assays were used to investigate the protective effects of ginsenoside Rg1 in the hippocampus. Results: Brain-derived neurotrophic factor/extracellular signal-regulated kinases (BDNF/ERK) signaling was altered in the hippocampus at 5 weeks after SCI. SCI attenuated neurogenesis and enhanced the expression of cleaved caspase-3 in the hippocampus; however, ginsenoside Rg1 attenuated cleaved caspase-3 expression and improved neurogenesis and BDNF/ERK signaling in the rat hippocampus. The results suggest that SCI affects BDNF/ERK signaling, and ginsenoside Rg1 can attenuate hippocampal damage after SCI. Conclusion: We speculate that the protective effects of ginsenoside Rg1 in hippocampal pathophysiology after SCI may involve BDNF/ERK signaling. Ginsenoside Rg1 shows promise as a therapeutic pharmaceutical product when seeking to counter SCI-induced hippocampal damage.